Potentiation of Morphine-Induced Antinociception by Propranolol: The Involvement of Dopamine and GABA Systems - Afify, Elham A.; Andijani, Najlaa M. (Frontiers in Pharmacology, 2017)
Tolerance to the analgesic effect of morphine is a major clinical problem which can be managed by co-administration of another drug. This study investigated the ability of propranolol to potentiate the antinociceptive action of morphine and the possible mechanisms underlying this effect. Antinociception was assessed in three nociceptive tests (thermal, hot plate), (visceral, acetic acid), and (inflammatory, formalin test) in mice and quantified by measuring the percent maximum possible effect, the percent inhibition of acetic acid-evoked writhing response, and the area under the curve values of number of flinches for treated mice, respectively. The study revealed that propranolol (0.25–20 mg/Kg, IP) administration did not produce analgesia in mice. However, 10 mg/Kg propranolol, enhanced the antinociceptive effect of sub-analgesic doses of morphine (0.2, 1, and 2 mg/Kg, IP) in the three nociceptive tests. It also shifted the dose response curve of morphine to the left. The combined effect of propranolol and morphine was attenuated by haloperidol (D2 receptor antagonist, 1.5 mg/Kg, IP), and bicuculline (GABAA receptor antagonist, 2 mg/Kg, IP). Repeated daily administration of propranolol (10 mg/Kg, IP) did not alter the nociceptive responses in the three pain tests, but it significantly potentiated morphine-induced antinociception in the hot plate, acetic acid-evoked writhing, and in the second phase of formalin tests. Together, the data suggest that a cross-talk exists between the opioidergic and adrenergic systems and implicate dopamine and GABA systems in this synergistic effect of morphine-propranolol combination. Propranolol may serve as an adjuvant therapy to potentiate the effect of opioid analgesics.